Effectiveness of a community-based cardiac rehabilitation program on functional independence and physical activity among patients with heart failure: a quasi-experimental study: Eficacia de un programa comunitario de rehabilitación cardíaca sobre la independencia funcional y la actividad física en pacientes con insuficiencia cardíaca: un estudio cuasiexperimental - Safruddin; Asri, Asri; Suswani, Andi; Risman, Muriyati; Aszrul (Gaceta Médica de Caracas, 2026)
Introduction: Heart failure (HF) is a leading cause of disability and mortality worldwide, especially in low-resource settings where access to hospital-based rehabilitation is limited. Community-based cardiac rehabilitation (CBCR) offers a practical and affordable model to enhance self-care and daily functioning among patients with HF. Objective: To determine the effectiveness of a six-week CBCR program in improving functional independence and physical activity in patients with chronic heart failure. Methods: A quasi-experimental pretest–posttest control-group study was conducted at two primary healthcare centers in Bulukumba, Indonesia, involving 252 stable HF patients (126 in the intervention group, 126 in the control group).